Atypical preeclampsia before 20 weeks of gestation with multicystic placenta, hyperreactio luteinalis, and elevated sFlt-1/PlGF ratio as manifestations of fetal triploidy: A case report - Harue Hayashida; Koji Nakamura; Koto Ukon; Kazuaki Sato; Kazuya Mimura; Mamoru Kakuda; Aska Toda; Tatsuya Miyake; Kosuke Hiramatsu; Toshihiro Kimura; Masayuki Endo; Tadashi Kimura (Elsevier, 2022)
Preeclampsia is one of the most common as well as most severe complications of pregnancy, characterized by new-onset hypertension and proteinuria or other organ dysfunction. It predominantly occurs after 20 weeks of gestation. Very rarely, it can be triggered earlier in some specific situations. Here we report a case of fetal triploidy presenting as an extraordinarily early-onset preeclampsia. A healthy 36-year-old multiparous woman who had conceived naturally was hospitalized due to acute-onset severe hypertension accompanied by proteinuria at 18 weeks of gestation. Laboratory testing ruled out the presence of underlying maternal disease. Ultrasound findings, including multicystic large placenta and multiple fetal anomalies, strongly suggested fetal triploidy. Maternal ovaries showed hyperreactio luteinalis. The soluble fms-like tyrosine kinase-1/ placental growth factor (sFlt-1/PlGF) ratio was elevated, at 270. Medical abortion was carried out at 19 weeks of gestation; thereafter, her symptoms quickly resolved. Fetal triploidy was confirmed by genetic testing. We should be aware that fetal disorders including triploidy as well as pre-existing maternal diseases can provoke such very early-onset preeclampsia. Fetal ultrasound evaluation is critical and the sFlt-1/PlGF ratio is important for prompt diagnosis and management to prevent adverse maternal outcomes associated with atypical preeclampsia before 20 weeks of gestation.